Anthropogenic expansions and their implications for land use and land cover in the Córrego do Galante watershed – SP - Simionatto, Henzo Henrique; Santos, Arthur Pereira dos; Américo-Pinheiro, Juliana Heloisa Pinê; Silva, Darllan Collins da Cunha e; Carvalho, Sergio Luis de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
This study aims to investigate, over a period of 35 years, the variations in land use and land cover in the Córrego do Galante watershed, located in Oeste Paulista. For this to be possible, it was necessary to choose data validated by the Annual Mapping of Coverage and Land Use in Brazil by MapBiomas and, using the Qgis software (3.30.1), the mask of the study area was delimited. After that, clippings of files were exported to the ArcGis software (10.5), in order to verify the spatial behavior of each class and, in addition, a statistical analysis software, Minitab, was used, where the classes found in the area were separated. of study in anthropic activities and non-anthropic activities, making it possible to assess the intensity of practices in the natural environment. A layout was prepared showing the variations in land use and land cover during the analyzed years. The results indicated that the analyzed area has been impacted by anthropogenic activity, where, in the beginning, it is characterized by livestock production and currently maintains a growing economy marked by the cultivation of sugarcane. It is concluded that there is a need to advance initiatives that enable the recovery of degraded points, aiming at the balance of ecosystem services and the mitigation of adversities and thus stimulate sustainable development in the activities carried out in this watershed.